APPLICATION OF ARTIFICIAL INTELLIGENCE-BASED INTERACTIVE LEARNING METHODS IN THE SUBJECT OF THE QUR'AN AND HADITH - Rodhiyana, Mu'allimah; Negara, Andika Kusuma; Adnan, Ahmad Hudaifi; Najwa Fikrotul Aulia (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
The lack of interactivity in learning Al-Qur’an and Hadith, especially in online lecture settings, remains a significant challenge amid the wave of educational digitalization. This issue becomes more pressing when students are not only learners but also active educators, whether in formal institutions or through online private tutoring. This study aims to describe the implementation of an interactive learning method based on Artificial Intelligence (AI) through webinar platforms in Qur’an and Hadith courses. A descriptive qualitative approach was employed. The sample was purposively selected, consisting of students from Class A of the 4th semester in the Islamic Education (PAI) Study Program, Faculty of Islamic Studies, Universitas Islam As-Syafi’iyah. This class was chosen due to its majority of students already being engaged in teaching, both directly and through online tutoring, making them suitable to assess the effectiveness of AI-based interactive learning from both learner and educator perspectives. Data were collected through participatory observation during the webinar sessions and reflective essays submitted by participants. The analysis involved data reduction, categorization, descriptive presentation, and conclusion drawing. The results show that the integration of AI promotes active participation, enhances digital engagement in religious learning, and provides a learning experience that aligns with contemporary teaching practices. This research highlights the importance of AI literacy among Islamic educators and the development of interactive media grounded in current technological advancements.